Implementasi Aplikasi Manajemen Mess (AMM) Berbasis Web - Rahma Dwi Cahyani; Hendrik Setyo Utomo (ULTIMA InfoSys, 2021)
The guesthouse management process of PT PPA is done conventionally, the Group Leader (GL) and the admin coordinate face to face for data collection or changes in employee data on the homestead dwellers. Temporary data collection is done by paper, then entered by MS. Excel. Reporting on homesteads is done by MS. Excel. If there is a change in data, then the reporting of the guest house is invalid. The researcher's goal is to implement a guesthouse management application to accommodate real-time data collection by the Group Leader. Reporting on the residents of the guesthouse can be done based on the date of the guesthouse management transaction. Testing is done by black-box testing and user acceptance test (UAT). All test results are functionally successful, and the test is carried out by the IT department. Based on the UAT test, the mes management application has an attractive appearance, is very easy to use, is very helpful for room relocation, is very in accordance with the proposed design, is very well organized by employees' rooms, is very suitable for the data entered and passwords can be hidden very well. Index Terms—guesthouse; homesteads; management; reporting; User Acceptance Test (UAT)